2017
DOI: 10.1182/blood-2017-03-776773
|View full text |Cite
|
Sign up to set email alerts
|

Expanded repertoire of RASGRP2 variants responsible for platelet dysfunction and severe bleeding

Abstract: Key Points Eleven pedigrees were identified with biallelic pathogenic variants in RASGPR2, which encodes platelet CalDAG-GEFI. CalDAG-GEFI deficiency is a severe, recessive, nonsyndromic platelet function disorder with defective aggregation to multiple agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 24 publications
3
41
0
Order By: Relevance
“…Data collection, human phenotype ontology (HPO) coding, and high-throughput sequencing were performed as previously reported. 18 Splice site, frameshift, stop-gain/ loss or start-loss variants were analyzed further if they were less frequent than 1 in 10 000 in the Exome Aggregation Consortium database and 1 in 100 in our in-house database. Candidate genes for BPD were identified by phenotype similarity regression 19 to allow for the high degree of phenotypic and genetic heterogeneity among the BPD cases.…”
Section: Recruitment Of Cases and Genetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Data collection, human phenotype ontology (HPO) coding, and high-throughput sequencing were performed as previously reported. 18 Splice site, frameshift, stop-gain/ loss or start-loss variants were analyzed further if they were less frequent than 1 in 10 000 in the Exome Aggregation Consortium database and 1 in 100 in our in-house database. Candidate genes for BPD were identified by phenotype similarity regression 19 to allow for the high degree of phenotypic and genetic heterogeneity among the BPD cases.…”
Section: Recruitment Of Cases and Genetic Analysismentioning
confidence: 99%
“…(A) Each BPD index case was coded using HPO terms relating to hematologic features and to phenotypes in other organ systems and underwent high-throughput sequencing. 18 Candidate genes for BPD were identified by similarity regression in which "baseline" and "alternate" statistical models are compared for every gene. 19 Under the baseline model, all cases are assumed to have the same log odds of carrying a rare variant.…”
mentioning
confidence: 99%
“…Given these numbers, it can be concluded that (1) only minimal changes in cytosolic calcium are required to mount a robust CalDAG-GEFI response, and (2) that some CalDAG-GEFI protein exists in an active conformation even in circulating, quiescent platelets. Consistent with these conclusions, complete CalDAG-GEFI deficiency is ill tolerated as it causes moderate to severe bleeding in humans and mice[51,5355,5860]. At the same time, CalDAG-GEFI/RAP1 signaling has to be restrained by RASA3 in circulating platelets to avoid severe thrombocytopenia and blood-lymphatic mixing in the developing embryo.…”
Section: Classical Hemostasis – Balancing Platelet Adhesiveness In CImentioning
confidence: 85%
“…The result is a near-immediate integration of second messenger generation and integrin activation. Lack of CalDAG-GEFI leads to impaired thrombus formation and bleeding[51,5355,5760]. …”
Section: Classical Hemostasis – Balancing Platelet Adhesiveness In CImentioning
confidence: 99%
“…Our studies have important clinical implications. Mutations in RasGRP2, the gene encoding CDGI, have recently been recognized as a new class of platelet function disorder . Although most variants lead to impaired expression of CDGI in patient platelets, some impair the function of an expressed protein.…”
Section: Discussionmentioning
confidence: 99%